EP1017 Prognostic and therapeutic factors for low-grade serous ovarian carcinoma: a multicentric, retrospective study of the turkish society of gynaecologic oncology. (1st November 2019) - Vatansever, D; Taskiran, C; Meydanlı, MM; Gungorduk, K; Akbayır, O; Yalcin, I; Demirkiran, F; Sozen, H; Ozgul, N; Celik, H; Onan, MA; Taskin, S; et al.
Abstract : Introduction/Background: Low-grade serous ovarian carcinoma (LGSOC) is a rare subtype of epithelial ovarian cancers (EOC), and is molecularly and clinically distinct from its high-grade counterpart. The aim of this study was to describe the clinico-pathological features of patients diagnosed with LGSOC and to analyse the factors affecting recurrence free survival (RFS) and overall survival (OS) rates. Methodology: Databases from 13 participating centres in Turkey were searched retrospectively for women who had been diagnosed with stage I to IV LGSOC between 1997 and 2018. Results: Overall 191 eligible women were analysed. Median age at diagnosis was 49 years (range, 21–84 years), and median Ca-125 value was 164 U/mL (range, 7–8685 U/ml). One hundred seventy-five (92%) patients underwent primary cytoreductive surgery and 65 patients (34%) were found to have FIGO stage I disease. Complete and optimal cytoreduction was achieved in 148 (77.5%) and 33 (17.3%) patients, respectively. Lymph node dissection was performed in 155 patients (81.2%), and 158 (83%) patients received adjuvant chemotherapy. Median follow-up period was 44 months (range, 2–208 months). Multivariate analysis showed that presence of endometriosis ( p = 0.012), LVSI ( p = 0.022), any residual disease ( p = 0.023) and FIGO stage II–IV ( p = 0.045) were negatively correlated with RFS, while only presence of residual disease ( p = 0.002) and FIGO stage II–IV ( p = 0.003) significantly shortened OS. Age, neoadjuvant or adjuvant chemotherapy, and lymph node metastasis did not affect survival outcomes. Conclusion: Patients with LGSOC diagnosed at an early stage have the best survival outcomes. The results of the current study suggest that maximal effort is warranted for complete cytoreduction since LGSOC appears to be relatively chemo-resistant in all settings. The prognostic role of both LVSI and endometriosis should be evaluated by further studies since both significantly affected RFS in this population. Disclosure: Nothing to disclose.